Effects of Calcium, Citric Acid, Ascorbic Acid, Vitamin D3 on the Efficacy of Microbial Phytase in Broiler Starters Fed Wheat-Based Diets I. Performance, Bone Mineralization and Ileal Digestibility - Afsharmanesh, M.; Pourreza, J. (International Journal of Poultry Science, 2005)
A study was conducted to determine the additive effects of calcium (Ca) levels and the enzyme phytase, organic acids (citric, ascorbic acid), vitamin D3 on broiler performance and nutrient digestibility (d 1 to 21) in wheat-based diet. Broilers were fed the following diets at either 7.9, or 9 g/kg of dietary Ca with: 1) a negative control wheat-based diet, 3.15 g/kg available phosphorus (P) (NC); 2) NC + 500 units Ronozyme™ P phytase/kg diet; 3) phytase + 20 g/kg citric acid; 4) phytase + citric acid + 200 mg/kg diet ascorbic acid; 5) phytase + citric acid + ascorbic acid + 200 μg/kg diet vitamin D3; 6) NC plus 1.35 g/kg available P. These 12 diets were supplemented with 50 mg/kg of xylanase (Ronozyme™ Wx, Roche) and fed to four replicates of 20 birds each. Phytase addition at the high Ca level increased body weight (BW), feed intake (FI), and tibia ash. Increased protein and P digestibility at the lower level of Ca and both levels of Ca, respectively was also present. Subsequent addition of citric and ascorbic acid to the low Ca diets increased BW and protein digestibility by 11.1 and 23%, respectively over the values obtained from the control diet. The BW of chicks that received the positive control diet were similar to those that received the phytase, organic acids and vitamin D3 supplemented low-Ca, low-P diet. The addition of phytase with citric acid, ascorbic acid, and vitamin D3 to the low Ca control diet improved BW and P digestibility by 18 and 60%, respectively. The data from this study shows that for broiler chickens, at low-P (3.15 g/kg), low-Ca (7.9 g/kg) diets supplemented with microbial phytase, organic acids and vitamin D3 improved feed conversion ratio (FCR) and gave a similar BW as a Ca- and P- adequate diets. These low P and Ca diets can result in a considerable reduction in the amount of excreted phosphorus and nitrogen.